ANALISIS TINGKAT KESEHATAN BANK UMUM SYARIAH MENGGUNAKAN METODE RGEC (STUDI KASUS PADA BANK PEMERINTAH DAERAH TAHUN 2019-2022) - Ade Yunanda Putra; Fera Sriyunianti; Dita Maretha Rissi (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2023)
This study seeks to assess and examine the health status of Sharia Commercial Banks for the years 2019 to 2022 by employing the RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) methodology. The type of research used is descriptive-quantitative, with the research subject being regional government banks in 2019–2022. The secondary data used in this study was obtained from each bank's official website. The analysis method used is RGEC aspects and tests for differences between years using the Mann-Whitney U-Test using SPSS v.25. The research results show that the assessment of the bank's health level from the RGEC aspect of Sharia Commercial Banks over the last 4 years, namely the 2019–2022 period, received Composite Rating 1 (PK 1), indicating that Regional Government Sharia Commercial Banks are in a very healthy condition. There is no discernible variation between the health level of banks from year to year throughout the 2019–2022 period, according to the results of evaluating the Sharia Commercial Banks' level of health using the RGEC value from the Mann-Whitney U-Test test results.